Local structure of amorphous sulfur in carbon–sulfur composites for all-solid-state lithium-sulfur batteries - Hiroshi Yamaguchi; Yu Ishihara; Yamato Haniu; Atsushi Sakuda; Akitoshi Hayashi; Kentaro Kobayashi; Satoshi Hiroi; Hiroki Yamada; Jo-chi Tseng; Seiya Shimono; Koji Ohara (Communications Chemistry)
Abstract All-solid-state (ASS) batteries are a promising solution to achieve carbon neutrality. ASS lithium–sulfur (Li-S) batteries stand out due to their improved safety, achieved by replacing organic solvents, which are prone to leakage and fire, with solid electrolytes. In addition, these batteries offer the benefits of higher capacity and the absence of rare metals. However, the low electronic conductivity of sulfur poses a major challenge for ASS Li-S batteries. To address this challenge, sulfur is often combined with porous carbon. Despite this standard practice, the local structure of sulfur in these composites remains unclear. Based on small-angle X-ray scattering and pair distribution function analysis, we discovered that sulfur in carbon–sulfur composites formed via melt diffusion is amorphous and primarily comprises S8 ring-shaped structures. The carbon–sulfur composite demonstrated a high specific capacity of 1625 mAh g−1 (97% of the theoretical specific capacity of sulfur). This remarkable performance is attributed to the extensive contact area between carbon and sulfur, which results in an excellent interface formed through melt diffusion. The insights gained into the local structure of sulfur and the analytical approaches employed enhanced our understanding of electrochemical reactions in ASS Li-S batteries, thereby aiding in the optimization of material design.